Exercise and the Aging Endothelium - Saeid Golbidi; Ismail Laher (Journal of Diabetes Research)
The endothelium plays a critical role in the maintenance of cardiovascular health by producing nitric oxide and other vasoactive materials. Aging is associated with a gradual decline in this functional aspect of endothelial regulation of cardiovascular homeostasis. Indeed, age is an independent risk factor for cardiovascular diseases and is in part an important factor in the increased exponential mortality rates from vascular disease such as myocardial infarction and stroke that occurs in the ageing population. There are a number of mechanisms suggested to explain age-related endothelial dysfunction. However, recent scientific studies have advanced the notion of oxidative stress and inflammation as the two major risk factors underlying aging and age-related diseases. Regular physical activity, known to have a favorable effect on cardiovascular health, can also improve the function of the ageing endothelium by modulating oxidative stress and inflammatory processes, as we discuss in this paper.